2021
DOI: 10.1021/acs.langmuir.1c02175
|View full text |Cite
|
Sign up to set email alerts
|

Using Nuclear Magnetic Resonance Spectroscopy to Probe Hydrogels Formed by Sodium Deoxycholate

Abstract: Hydrogels of bile acids and their salts are promising materials for drug delivery, cellular immobilization, and other applications. However, these hydrogels are poorly understood at the molecular level, and further study is needed to allow improved materials to be created by design. We have used NMR spectroscopy to probe hydrogels formed from mixtures of formic acid and sodium deoxycholate (NaDC), a common bile acid salt. By assaying the ratio of deoxycholate molecules that are immobilized as part of the fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…59−64 Our group has worked extensively with these materials, and we have examined hydrogels formed by derivatives of bile acids in conjunction with carboxylic acids, 65 the sequestration of CO 2 by hydrogels containing bile acid salts, 66 and related topics. 51,67,68 ■ RESULTS AND DISCUSSION LCA has low solubility in water at pH 7, but solutions of the corresponding NH 4 + salt with concentrations of about 50 mM (2 wt %) can be obtained by warming aqueous mixtures made by combining LCA and NH 3 in a 1:16 molar ratio. Cooling the solutions to 25 °C led reproducibly to the formation of hydrogels, which were characterized by standard methods, including optical microscopy, electron microscopy, and rheological measurements.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…59−64 Our group has worked extensively with these materials, and we have examined hydrogels formed by derivatives of bile acids in conjunction with carboxylic acids, 65 the sequestration of CO 2 by hydrogels containing bile acid salts, 66 and related topics. 51,67,68 ■ RESULTS AND DISCUSSION LCA has low solubility in water at pH 7, but solutions of the corresponding NH 4 + salt with concentrations of about 50 mM (2 wt %) can be obtained by warming aqueous mixtures made by combining LCA and NH 3 in a 1:16 molar ratio. Cooling the solutions to 25 °C led reproducibly to the formation of hydrogels, which were characterized by standard methods, including optical microscopy, electron microscopy, and rheological measurements.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As illustrated by LCA and DCA, bile acids have amphiphilic structures in which an extended convex hydrophobic surface is combined with hydrophilic hydroxyl and carboxyl groups. This amphiphilicity allows bile acids, their salts, and other derivatives to form biocompatible hydrogels that are promising materials for use in drug delivery, cellular immobilization, and other applications. Our group has worked extensively with these materials, and we have examined hydrogels formed by derivatives of bile acids in conjunction with carboxylic acids, the sequestration of CO 2 by hydrogels containing bile acid salts, and related topics. ,, …”
Section: Introductionmentioning
confidence: 99%
“…57−62 Our group has worked actively in these areas, 15,49,63−66 and we have studied hydrogels formed by mixing carboxylic acids with derivatives of bile acids, 63 ways to sequester CO 2 in hydrogels containing bile acid salts, 64 and other topics. 65,66 Experience with bile acids and their derivatives has shown that a properly adjusted level of solubility in water is a prerequisite for hydrogelation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These compounds have a tetracyclic steroidal structure that includes an extended convex hydrophobic face and an opposing concave hydrophilic face with hydroxyl and carboxyl groups. The resulting amphiphilicity gives rise to the formation of biocompatible hydrogels that are promising for use in drug delivery, cellular immobilization, and other applications. Our group has worked actively in these areas, ,, and we have studied hydrogels formed by mixing carboxylic acids with derivatives of bile acids, ways to sequester CO 2 in hydrogels containing bile acid salts, and other topics. , Experience with bile acids and their derivatives has shown that a properly adjusted level of solubility in water is a prerequisite for hydrogelation.…”
Section: Introductionmentioning
confidence: 99%
“…This special issue celebrates her career with contributions from colleagues across the world. The included papers represent many topical areas, including microgels, elastomers, microbubbles, microemulsions, supramolecular assemblies, and thin films, with critical physical properties enabling applications as broad-ranging as carbon capture, medicine, and electronics. Nonetheless, many of the papers are fundamental in nature, reflecting Professor Winnik’s enduring commitment to and interest in basic colloid and interfacial science.…”
mentioning
confidence: 99%